Gene expression profiles of oil palm leaves from different oil yields and genetic population: Transcriptomic dataset - Ardha Apriyanto; Reza Ernawan; Mokhamad Krishna Adianto Putra; Ricki Susilo; Walter Ajambang; Adi Pancoro; Cahyo Sri Wibowo (Data in Brief, 2023)
Oil palm (Elaeis guineensis Jacq.) is one of the most important oil-producing crops in the world. However, the demand for oil from this crop is expected to increase in the future. A comparative gene expression profile of the oil palm leaves was needed in order to understand the key factors that influence the oil production. Here, we reported an RNA-seq dataset from three different oil yields and three different genetic populations of oil palm. All raw sequencing reads were obtained from an Illumina NextSeq 500 platform. We also provide a list of the genes and their expression levels resulting from the RNA-sequencing. This transcriptomic dataset will provide a valuable resource for increasing oil yield.